a) g(3) = -182
b) g(0) = 7
c) g(-1) = 70
Step-by-step explanation:
![\begin{gathered} \text{Given:} \\ g(x)\text{ = }7\text{ - 63x} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fw4kn4x837mavve23juqgcbfgpk99k4g6a.png)
a) g(3): To get this, we will substitute 3 for x in the function g(x)
![\begin{gathered} \text{x = 3} \\ g(3)=\text{ 7 - 63(3) = 7 - 189} \\ g(3)\text{ = }-182 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bzrfos99m6l1ctol81qdc6ssewxhyc5wft.png)
b) g(0): To get this, we will substitute 0 for x in function g(x)
![\begin{gathered} x\text{ = 0} \\ g(0)\text{ = 7 - 63(0) = 7 - 0} \\ g(0)\text{ = 7} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5l943f1v5y7jnemt1kj4iofxyr8droi7tg.png)
c) g(-1): To get this, we will substitute -1 for x in function g(x)
![\begin{gathered} x\text{ = -1} \\ g(-1)\text{ = 7 - 63(-1)} \\ mu\text{ltiplication of same signs give positive sign} \\ g(-1)\text{ = 7 + 63} \\ g(-1)\text{ = 70} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3q3d1q1cllihguaupu1axwmukp0drvbepr.png)